Metabolomics for Prediction of Relapse in Graves' Disease: Observational Pilot Study - Struja, Tristan; Eckart, Andreas; Kutz, Alexander; Huber, Andreas; Neyer, Peter; Kraenzlin, Marius; Mueller, Beat; Meier, Christian; Bernasconi, Luca; Schuetz, Philipp (Frontiers in Endocrinology, 2018)
Background: There is a lack of biochemical markers for early prediction of relapse in patients with Graves’ disease [GD], which may help to direct treatment decisions. We assessed the prognostic ability of a high-throughput proton NMR metabolomic profile to predict relapse in a well characterized cohort of GD patients. Methods: Observational study investigating patients presenting with GD at a Swiss hospital endocrine referral center and an associated endocrine outpatient clinic. We measured 227 metabolic markers in the blood of patients before treatment initiation. Main outcome was relapse of hyperthyroidism within 18months after stop of anti-thyroid drugs. We used ROC analysis with AUC to assess discrimination. Results: Of 69 included patients 18 (26%) patients had a relapse of disease. The clinical GREAT score had an AUC of 0.68 (95% CI 0.63–0.70) to predict relapse. When looking at the metabolomic markers, univariate analysis revealed pyruvate and triglycerides in medium VLDL as predictors with AUCs of 0.73 (95% CI 0.58 – 0.84) and 0.67 (95% CI 0.53 – 0.80), respectively. All other metabolomic markers had lower AUCs. Conclusion: Overall, metabolomic markers in our pilot study had low to moderate prognostic potential for prediction of relapse of GD, with pyruvate and triglycerides being candidates with acceptable discriminatory abilities. Our data need validation in future larger trials.